Examining Mediating Role Of Coffee Shop Customer Satisfaction In Indonesia - Satria Tirtayasa; Hazmanan Kahir; Nasib, Nasib (Cita konsultindo, 2024)
Customer loyalty is the tendency of customers to buy a product or use the services provided by a company with a high level of consistency. This study aimed to determine the effect of product and service quality on customer loyalty through customer satisfaction. The population in this study were coffee shop customers in Medan City, whose numbers were unknown. The research sample was 100 coffee shop customers in Medan City (Lemeshow method). The data collection technique uses a direct survey, where respondents answer questions directly via Google Forms. The data analysis technique used is SEM-PLS. The research results obtained consist of the following: there is a positive and insignificant influence between product quality on customer loyalty, there is a positive and insignificant influence between product quality on customer satisfaction, there is a positive and significant influence between customer satisfaction on customer loyalty, This study found that there is a positive and significant influence between customer satisfaction on customer loyalty. This study also proves the mediating role of customer satisfaction between the effect of product quality on customer loyalty and the mediating role of customer satisfaction between the effect of service quality on customer loyalty. This study shows the important role of product quality and service in increasing customer satisfaction in coffee shop customers in Medan. This study also proves the mediating role of customer satisfaction in the relationship between product quality and service on coffee shop customer loyalty in Medan.